MENGIDENTIFIKASI KEBUTUHAN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MATERI SHOLAT DI SDN 3 MARIA TAHUN PELAJARA 2022/2023 - Junaidin Junaidin (Fitrah, 2022)
This study aims to identify the learning needs of students in the subject of Islamic Religious Education and Budi Pekerti in the class VI . This research uses a literature approach and case studies. These approaches aim to explore theory, adapt to field conditions as evidenced by experiments. The results of this study explain that the need is a situation where there is a gap between facts and expectations, which is indicated by the existing difference. The various needs in learning are not interpreted broadly as Maslow's theory but are still within the scope of learning. The kinds of needs, namely; normative, comparative, felt neds, expressions (expressed neds), anticipation, and unexpected critical circumstances. In addition, related to the identification of learning needs, means collaborating between problem identification and problem analysis, identification aims to collect data on the existence of gaps in learning, then analysis aims to find out the causes of these gaps. This can be done in seven steps, namely; identify problems, validate problems, formulate needs, formulate goals (competencies), adjust old goals to new goals, validate goals that have been adjusted, and finally prioritize goals.